Pathways to Program Success: A Qualitative Comparative Analysis (QCA) of Communities Putting Prevention to Work Case Study Programs. Issue 2 (March 2017) - Kane, Heather; Hinnant, Laurie; Day, Kristine; Council, Mary; Tzeng, Janice; Soler, Robin; Chambard, Megan; Roussel, Amy; Heirendt, Wendy
Abstract : Objective: To examine the elements of capacity, a measure of organizational resources supporting program implementation that result in successful completion of public health program objectives in a public health initiative serving 50 communities. Design: We used crisp set Qualitative Comparative Analysis (QCA) to analyze case study and quantitative data collected during the evaluation of the Communities Putting Prevention to Work (CPPW) program. Setting: CPPW awardee program staff and partners implemented evidence-based public health improvements in counties, cities, and organizations (eg, worksites, schools). Participants: Data came from case studies of 22 CPPW awardee programs that implemented evidence-based, community- and organizational-level public health improvements. Intervention: Program staff implemented a range of evidence-based public health improvements related to tobacco control and obesity prevention. Main Outcome Measure: The outcome measure was completion of approximately 60% of work plan objectives. Results: Analysis of the capacity conditions revealed 2 combinations for completing most work plan objectives: (1) having experience implementing public health improvements in combination with having a history of collaboration with partners; and (2) not having experience implementing public health improvements in combination with having leadership support. Conclusion: Awardees have varying levels of capacity. The combinations identified in this analysis provide important insights into how awardees with different combinations of elements of capacity achieved most of their work plan objectives. Even when awardees lack some elements of capacity, they can build it through strategies such as hiring staff and engaging new partners with expertise. In some instances, lacking 1 or more elements of capacity did not prevent an awardee from successfully completing objectives. These findings can help funders and practitioners recognize and assemble different aspects of capacity to achieve more successful programs; awardees can draw on extant organizational strengths to compensate when other aspects of capacity are absent. Abstract : Supplemental Digital Content is Available in the Text.